Phenotyping root architecture in diverse wheat germplasm - Atkinson, Jonathan A. (2016)
Wheat is a crop of global importance accounting for 20% of global calorie consumption and a similar percentage of the daily protein for 2.5 billion people in less developed countries. To meet the food production demands of a predicted global population of 9 billion people by 2050, wheat yields need to increase by 1.7% per annum, whilst facing the added pressures of reduced fertilizer inputs and potentially reduced land availability. Plant root systems are key for efficient water and nutrient uptake and thus have a direct impact on yield, and yet there has been competitively little research into root system improvement. A high-throughput root phenotyping pipeline for wheat seedlings was designed consisting of a germination paper-based growth system combined with image segmentation and analysis software. A number of lines from the A.E. Watkins landrace population were characterised to test the final pipeline design. The pipeline was then utilized to phenotype a population of 94 lines from a doubled haploid population for quantitative trait loci (QTL) discovery. In total, 29 root QTL were discovered, with 2 loci co-localising with QTL for grain yield and nitrogen uptake efficiency discovered in field trials. Modern wheat varieties may have limited genetic diversity, due to changes in ploidy throughout evolution and subsequent domestication. With this in mind, thirty five ancient wheat relatives and eighteen amphidiploid hybrids were phenotyped for seedling root architectural traits, to determine the amount of phenotypic variation within ancient wheat species, and whether this variation can be transferred to modern varieties. The utilization of seedling root trait phenotyping is discussed and future research directions are identified.